The Role of Smarthome Technology for Improving Supply Chain and Perceived Value on Housing Retailer - Bob Foster; Ari Purno Wahyu; Fitriani Reyta; Jumadil Saputra (International Journal of Supply Chain Management, 2019)
Abstract- Smart building can be a procedure for developing supply chain in civil industry. The current type of housing in Indonesia is classified into several clusters and has varying prices, from prices of hundreds of millions to billions. For homes that have a price of millions, providing comfortable facilities,it is a must such as smart home systems that offer additional safety features, running by IoT (Internet of Things) technology where the owner can control and monitor via smartphones. This kind of system will certainly not be available on simple housing types or mortgages. To use this system, the owner or housing retailer will issue a large amount of cost used for the installation and installation. Some developer offered a smart home technology with a relativelyhigh price, which is around the price of 20 million to a dozen million IDR which not include the usual maintenance and installation of the system. This condition overcomes the problem that housing retailer often difficult to sell a house with extra smart home packages. Mostly, the onlyhigh-income consumer can buy a house with smart home features. This problem is the detailed background for this research that aims to design software of smart home that affordable, and to optimize the value of housing used the descriptive quantitative method with a waterfall system as a software development model. At the end reach purposed that the smart concept can be installed at home or housing so that not only owned by a high-end consumer but also with middle to lower consumption.